The Head Master of Strategy In Developing Religious Academic Quality Culture - Husni, Muhammad (EDUKASI: Jurnal Pendidikan Islam, 2018)
The strategy of developing a culture of religious academic quality includes: planning, implementation, and evaluation. The method of this research uses descriptive qualitative method. The purpose to analyze and find the efforts of Head Master in developing culture of academic religious quality. in developing the culture of quality that is SWOT strategy which is contained in vision, velue, program, and target of School. The research findings formed vision of school mission, goals and objectives, and effort of schoolr principal in developing culture of religious academic quality.